George Mellis Douglas (1875-1963) - Finnie, Richard S. (ARCTIC, 1985)
George M. Douglas was one of the most efficient and well-informed explorers of the Mackenzie District, particularly the northerly reaches of Great Bear Lake and the Coppermine River as far as the arctic coast, during the early years of the twentieth century. A lean, muscular six-footer, he was a pioneer who opened up new vistas for mineral investigation and development. Yet he is chiefly known for his only book, Land Forlorn, which, published in 1914, is noteworthy for its accuracy, attention to detail, and superb photographs. It stands as one of the classics of northern literature. . He went to sea as a marine engineer between 1897 and 1900 and then began a career in Mexico and Arizona as an engineer, later as a consulting engineer, until 1940. His work in the Southwest was interrupted by the first of his northern explorations. This was for a 1911-1912 expedition to Great Bear Lake, the Dismal Lakes, and the lower Coppermine River to search for copper deposits. . The three-man party, headed by George Douglas, included his brother, Lionel, a master mariner, and Dr. August Sandburg, a geologist. . The Douglas party tracked up the swift-flowing Great Bear River with a York boat to Great Bear Lake, towing a canoe. They sailed across the lake to the northeasterly corner at the mouth of the Dease River, where Lionel Douglas built a substantial cabin for the winter. Meanwhile, George Douglas and August Sandburg canoed up the Dease to the Dismal Lakes and thence to the Kendall River and the Coppermine. They explored the Coppermine Mountains during the first season before returning to the cabin. . In the spring of 1912 the Douglas party returned to the Coppermine and found the extent of the mineralized area to be much greater than had been supposed, the width of the belt being about 25 kilometres. It was deemed significant enough to justify more extensive prospecting, but the effects of World War I and the copper industry discouraged it. The party ranged as far as Coronation Gulf, meeting some of the Copper Inuit but ...